2020
DOI: 10.26655/jrweedsci.2020.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The study was conducted with the aim of assessing the distribution and abundance of invasive alien plant species (IAPS) in two administrative Zones (1 and 3) of the Afar region. Data were collected using systematic sampling technique and regular intervals of 10 km were used during the field survey. The following weeds Calotropis procera, Cryptostegia grandiflora, Jatropha curcas, Lantana camara, Opuntia stricta, Parkinsonia aculeata, Parthenium hysterophorus, Prosopis juliflora, Senna occidentalis, and Solanum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…This result indicated the domination and colonization of Prosopis along roadsides. Similarly, Shashitu (2008) also observed that Prosopis invasion was high around roadsides than other habitats since Prosopis seeds were distributed from one place to another by animals through their dung along roadsides. Prosopis infestation around habitation areas ranged from abundant (75-100%) to frequent (30-50%) levels (Figure 4).…”
Section: Distribution and Abundance Of Prosopis Julifloramentioning
confidence: 83%
“…This result indicated the domination and colonization of Prosopis along roadsides. Similarly, Shashitu (2008) also observed that Prosopis invasion was high around roadsides than other habitats since Prosopis seeds were distributed from one place to another by animals through their dung along roadsides. Prosopis infestation around habitation areas ranged from abundant (75-100%) to frequent (30-50%) levels (Figure 4).…”
Section: Distribution and Abundance Of Prosopis Julifloramentioning
confidence: 83%